The Myths That Made America : An Introduction to American Studies - Paul, Heike (2014)
This essential introduction to American studies examines the core foundational myths upon which the nation is based and which still determine discussions of US-American identities today. These myths include the myth of »discovery,« the Pocahontas myth, the myth of the Promised Land, the myth of the Founding Fathers, the melting pot myth, the myth of the West, and the myth of the self-made man. The chapters provide extended analyses of each of these myths, using examples from popular culture, literature, memorial culture, school books, and every-day life. Including visual material as well as study questions, this book will be of interest to any student of American studies and will foster an understanding of the United States of America as an imagined community by analyzing the foundational role of myths in the process of nation building...